Fatalities in opioid agonist treatment with long-acting injectable buprenorphine - Häkkinen, Margareeta; Mariottini, Claudia; Kriikku, Pirkko; Ojanperä, Ilkka (Springer Science and Business Media LLC, 2025)
Purpose
Long-acting injectable buprenorphine (LAI BUP) is a novel opioid agonist treatment (OAT) medication with several benefits for patients, OAT units, and society. We present a case series of fatalities in OAT with LAI BUP.
Methods
This was an audit of OAT patient records, supplemented with results of post-mortem (PM) investigation. We started with all deaths (N = 604) between 2018 and 2020 in Finland with a buprenorphine or norbuprenorphine finding in PM toxicology and with known substance use history or concomitant findings of illicit drugs. We then examined the patient records of the 43 individuals in OAT at the time of death. We analyzed information on OAT medication, OAT structure, and performance, including concomitant substance use, and PM findings.
Results
Ten LAI BUP patients died during the study period, all of them in 2020, out of the 18 patients receiving some OAT that year. Among the LAI BUP patients, four died from buprenorphine poisoning. Eight patients had PM findings of abused drugs, always including unprescribed benzodiazepines. Two patients showed signs of additional buprenorphine use of which their OAT unit was unaware. Three patients were classified as non-compliant with OAT but had received no extra support to tackle their situation. Visits to the OAT clinic had mainly occurred only on injection days.
Conclusions
LAI BUP comprised 56% of OAT medication among all deceased OAT patients in 2020. Despite its recognized benefits, LAI BUP treatment was associated with deaths. Psychosocial support among the deceased LAI BUP patients seemed inadequate.